2012
DOI: 10.1016/j.jcma.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological characterization of Charcot–Marie–Tooth disease type 1A in Taiwan

Abstract: This study provides basic electrophysiological knowledge about CMT1A in Taiwan. The findings also suggest that the electrophysiological variability in the CMT1A cohort may be at least partially attributable to unknown genetic factors. These data emphasize the role of MNCV in the clinical assessment of CMT1A. A median or ulnar MNCV below 38 m/s can be a sensitive criterion for supporting the diagnosis of CMT1A. A median MNCV can sometimes help to distinguish CMT1A from CMT1B, and CMT1A should be considered in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is of interest that, although these findings have already been noted in previous reports [2,11], the current notion is that NCV does not change significantly through the life of CMT1A patients [7][8][9]. Birouk and colleagues found in their large sample of CMT1A patients that NCV increased with age and they interpreted the more evident lower NCV in younger patients as an expression of early diagnosis in younger CMT1A patients due to their more severe symptoms [2].…”
Section: Discussionmentioning
confidence: 68%
“…It is of interest that, although these findings have already been noted in previous reports [2,11], the current notion is that NCV does not change significantly through the life of CMT1A patients [7][8][9]. Birouk and colleagues found in their large sample of CMT1A patients that NCV increased with age and they interpreted the more evident lower NCV in younger patients as an expression of early diagnosis in younger CMT1A patients due to their more severe symptoms [2].…”
Section: Discussionmentioning
confidence: 68%
“…In the proband, the severe course and the results of the neurophysiological findings suggested the diagnosis of CMT type 1. Differentiation between CMT1 and CTM2 is not easy since both the two demyelinating and axonal types share some feature in common with the exception in the case of CMT2 of a less severe course of the symptoms and the findings of nerve conduction velocity which are usually not involved or only partially [ 6 8 ]. The proband showed two additional signs: congenital severe inguinal hernia that required a rapid surgical correction and a cranial neuropathy causing bilateral sensorineural hearing loss, which was treated with cochlear implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Dejerine-Sottas syndrome [ 5 , 6 ], or onset in the late adulthood, has been described occasionally. The motor nerve conduction velocity (MNCV) in median nerves reduces severely [ 2 , 7 ] but slightly increases with the age of MNCV, potentially due to myelin thickness remodeling that occurs later in CMT1A patients [ 8 ]. Previous studies have shown that the compound muscle action potential amplitude (CMAP) was reduced from an early age, and its typical increase with age was attenuated [ 9 ].…”
Section: Introductionmentioning
confidence: 99%